E PENGARUH SUBSTITUSI SERAT AMPAS TEBU TERHADAP KARAKTERISTIK PIRING BIODEGRADABLE BERBASIS GLUKOMANAN DAN KARAGENAN - Rusdianto, Andrew Setiawan; Soekarno, Siswoyo; Adindra, Plasida Geustin (Jurnal Penelitian Sains dan Teknologi Indonesia, 2025)
Bioplastics are alternative packaging made from natural polymers, which have the properties of being biodegradable, reduce environmental pollution and are safe for health because they do not contain toxic substances. Bioplastics are made from natural materials. It is hoped that the existence of environmentally friendly plate products can reduce the use of plastic plates in the community so as to reduce the accumulation of excessive plastic waste. The addition of bagasse to environmentally friendly plate products is expected to improve their mechanical properties. There are 3 variations of bagasse fiber size used, namely 60 mesh, 1mm and 3mm. The purpose of this study was to determine the effect of bagasse size variation on tensile strength, elongation, water resistance and biodegradability of eco-friendly plates and to get the best formulation of bagasse size variation as raw material for making eco-friendly plates. The manufacture of environmentally friendly eco-friendly plates used a completely randomized design with one factor and 3 repetitions. Observations made included biodegradability test, water resistance test, tensile strength test and elongation test. The results showed that of the three treatments, the variation of adding 60 mesh bagasse (A) was the best formulation for environmentally friendly plate products. Bioplastic products for plate shape are expected to have strong mechanical properties and can be degraded in the environment.